PEMANTAUAN BALITA BERAT BADAN TIDAK NAIK YANG MENDAPATKAN TAMBAHAN ASUPAN GIZI DI WILAYAH KERJA PUKESMAS MUARA BATU - Kiki Asrifa Dinen; Hafidhatun Nisa; Ully Fitria (PT. Penerbit Riset Sadwa, 2025)
The reduction of stunting prevalence in Indonesia remains a major challenge, with stunting prevalence not yet reaching the target of 14% by 2024. One of the efforts to combat stunting is by providing supplementary nutrition to toddlers. This study aims to evaluate the impact of providing supplementary nutrition on improving the nutritional status of toddlers in Muara Batu District, Aceh Utara, as part of efforts to address stunting. Stunting is a chronic nutritional issue that can affect physical growth, cognitive development, and long-term health outcomes for children. Using a descriptive quantitative method with a field survey approach, this study involved 12 toddlers who received additional nutrition. Data were collected through direct observation at posyandu (integrated health posts), interviews with parents, and statistical analysis using the Friedman test to identify significant changes in toddlers' nutritional status. The results of the study showed that the provision of supplementary nutrition had a significant positive impact on the toddlers' weight gain (p < 0.05), which could potentially reduce the risk of stunting. However, the effectiveness of this program is also influenced by other factors such as parents' knowledge of proper nutrition, accessibility to posyandu, as well as environmental conditions like sanitation and access to clean water. This study suggests the need for a comprehensive approach to tackling stunting, including nutrition education for parents, improving access to health services, and improving environmental conditions that support children's growth and development. The findings underscore the importance of early intervention and collaboration between the government, health workers, and the community to ensure the success of the supplementary nutrition program and reduce the prevalence of stunting in toddlers.